VIGNETTE ILLUSTRATION ARTWORKS WITH THE SUBJECT MATTER OF MYTHOLOGICAL ANIMALS FROM JAVA AND BALI - Wiyati, Lungsari Cendraning; Arif Fiyanto (Eduarts: Jurnal Pendidikan Seni, 2025)
The purpose of this study project is to create vignette illustrations with the theme of mythological animals from Java and Bali as an educational medium that is able to convey local cultural, historical, and philosophical values. In this work, the author intends to create two artworks with a total of five Javanese Balinese mythological animals namely Naga Antaboga, Naga Basuki, and Naga Taksaka, Bedawang Nala, and Garuda. This work shows that a visual approach based on fine arts can be an effective means of conveying local cultural values creatively and communicatively, while showing the historical and cultural links between the two regions. It is hoped that this work can inspire other artists to explore local culture as a source of creative ideas, and become part of the effort to preserve cultural heritage through a fresher, more imaginative and relevant approach. This project is expected to be useful in enriching the diversity of contemporary art, building cultural awareness in the younger generation, and becoming an alternative learning media that fosters appreciation for the richness of Indonesian mythology.